2017
DOI: 10.1007/s40572-017-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neurotoxicity of Traffic-Related Air Pollution: Focus on Autism

Abstract: Purpose of Review Epidemiological and animal studies suggest that air pollution may negatively affect the central nervous system (CNS) and contribute to CNS diseases. Traffic-related air pollution is a major contributor to global air pollution, and diesel exhaust (DE) is its most important component. Recent findings Several studies suggest that young individuals may be particularly susceptible to air pollution-induced neurotoxicity, and that perinatal exposure may cause or contribute to developmental disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 162 publications
1
36
0
2
Order By: Relevance
“…Exposure to NO 2 may increase the risk of schizophrenia admissions through increased neuroinflammation and oxidative stress,28 29 as supported by the following findings from animal studies: associations between diesel exhaust inhalation and neuroinflammation in brain regions,30 relationship between NO 2 inhalation and brain pathology, lower antioxidant defences and deregulation of apoptosis-related genes expression,31 links between diesel exhaust and microglial activation and upregulation of oxidative stress,28 and associations between vehicle emissions and anxiety-like behaviour, depression-like behaviour, neurobehavioural as well as cognitive deficits 24. Epidemiological research also indicated that traffic-related air pollution was associated with autism and decreased cognitive function 11 32 33.…”
Section: Discussionmentioning
confidence: 96%
“…Exposure to NO 2 may increase the risk of schizophrenia admissions through increased neuroinflammation and oxidative stress,28 29 as supported by the following findings from animal studies: associations between diesel exhaust inhalation and neuroinflammation in brain regions,30 relationship between NO 2 inhalation and brain pathology, lower antioxidant defences and deregulation of apoptosis-related genes expression,31 links between diesel exhaust and microglial activation and upregulation of oxidative stress,28 and associations between vehicle emissions and anxiety-like behaviour, depression-like behaviour, neurobehavioural as well as cognitive deficits 24. Epidemiological research also indicated that traffic-related air pollution was associated with autism and decreased cognitive function 11 32 33.…”
Section: Discussionmentioning
confidence: 96%
“…Although genetics likely plays an important role in ASD, environmental exposures to pollutants particularly during the early life periods could be another potential risk factor [6,7]. Environmental factors such as exposure to air pollution may contribute to ASD etiology [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence accumulated from human epidemiological and animal studies indicates that ambient air pollution may be associated with diseases of the central nervous system (CNS) [34]. Children are particularly susceptible to air pollutants, and pre-and/or postnatal exposure may negatively affect their CNS [35]. Recently, several investigation studies have integrated magnetic resonance imaging of the brain with epidemiology, showing that long-term exposure to air pollution might have adverse impacts on the human brain [36].…”
Section: Discussionmentioning
confidence: 99%